The Relationship Between Nutritional Knowledge and Eating Patterns Among Fifth Grade Students in Public Elementary Schools in Kediri District - Arfinal, Arfinal; Kusmiyati, Kusmiyati; Rasmi, Dewa Ayu Citra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nutritional knowledge is a crucial factor in determining health and the balance between physical and mental development. Nutritional knowledge plays a crucial role in shaping a person's eating habits because it influences the types and amounts of food they choose. This study aimed to examine the relationship between nutritional knowledge and eating patterns among fifth-grade students in public elementary schools in Kediri District, West Lombok Regency, Indonesia. Using a quantitative approach with a cross-sectional design, data were collected from 221 students selected through simple random sampling from eight schools. Nutritional knowledge was measured using a multiple-choice test, while eating patterns were assessed through a structured questionnaire. Data analysis involved Chi-Square and Pearson correlation tests. The results showed a significant relationship between nutritional knowledge and eating patterns (p = 0.001), with a moderate positive correlation (r = 0.530). Most students demonstrated moderate nutritional knowledge (46.6%) and good eating patterns (66.5%). These findings suggest that higher nutritional knowledge is associated with healthier eating patterns. However, knowledge alone is not sufficient to ensure optimal eating behavior, as other factors such as family environment, food availability, and habits also play important roles. Strengthening nutrition education in schools and engaging parents in promoting healthy eating are recommended to improve students' dietary habits.